PENGARUH PENGGUNAAN MODEL PEMBELAJARAN WORD SQUARE TERHADAP KEAKTIFAN DAN HASIL BELAJAR IPA DI MI HIDAYATUL MUBTADIIN WATES SUMBERGEMPOL TULUNGAGUNG - Ira Armisa; Uswatun Hasanah (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2022)
Varied learning causes students to be more active in learning, and vice versa. If learning is not student-centered, students will tend to be passive and learning outcomes will also not be optimal. For this reason, teachers need to combine various learning models so that learning becomes more varied and not boring, one of which in this study uses the word square. This study aims to determine the effect of using the word square learning model on learning activity, learning outcomes, as well as student activity and learning outcomes simultaneously in science subjects. This research was conducted at MI Hidayatul Mubtadiin Wates Sumbergempol Tulungagung. The method used is a quasi-experimental research, with a sampling technique using probability sampling. The population and samples were the same, namely 38 students of class V MI Hidayatul Mubtadiin who were grouped into the experimental class and the control class. (1) The results of the activity questionnaire were obtained by Sig. 0.002 < 0.05, then Ha is accepted (2) the results of the T test of learning outcomes obtained Sig. 0.026 <0.05, then Ha is accepted (3) the results of the manova test, activeness questionnaires and learning outcomes tests are obtained by Sig. 0.007 < 0.05, then Ha is accepted. So it can be concluded that there are differences in activity, learning outcomes, as well as student activity and learning outcomes after using the word squarein science subjects.